Ecdysone-induced expression of the caspase DRONC during hormone-dependent programmed cell death in Drosophila is regulated by Broad-Complex - Cakouros, Dimitrios (The Rockefeller University Press, 2002)
The steroid hormone ecdysone regulates both cell differentiation and cell death during insect metamorphosis, by hierarchical transcriptional regulation of a number of genes, including the Broad-Complex (BR-C), the zinc finger family of transcription factors. These genes in turn regulate the transcription of a number of downstream genes. DRONC, a key apical caspase in Drosophila, is the only known caspase that is transcriptionally regulated by ecdysone during development. We demonstrate that dronc gene expression is ablated or reduced in BR-C mutant flies. Using RNA interference in an ecdysone-responsive Drosophila cell line, we show that DRONC is essential for ecdysone-mediated cell death, and that dronc upregulation in these cells is controlled by BR-C. Finally, we show that the dronc promoter has BR-C interaction sites, and that it can be transactivated by a specific isoform of BR-C. These results indicate that BR-C plays a key role in ecdysone-mediated caspase regulation.